[Recensão a] Gunther Pallaver, Michael Gehler, Maurizio Cau, (eds.) (2018). Populism, populists, and the crisis of political parties. A comparison of Italy, Austria, and Germany 1990-2015 - Dina Sebastião (Revista de História das Ideias, 2019)
https://doi.org/10.14195/2183-8925_37_19